2011
DOI: 10.1097/bte.0b013e31823a59f2
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Considerations for Rotator Cuff Repairs

Abstract: The ideal rotator cuff repair should have strong initial fixation strength to resist early structural failure and high footprint contact pressure to assist biological healing. Fixation strength can be enhanced by using more suture anchors in the repair construct and by placing anchors in area of high bone density such as the proximal part of the tuberosities. High footprint contact pressure can be achieved by using tension band repair constructs such as inverted mattress and suture bridge technique. These tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Rotator cuff tears are among the most common causes of pain and functional disability in the shoulder and commonly affect the supraspinatus tendon. 5 , 7 , 9 , 18 , 20 Integrity of the supraspinatus is vital for overhead shoulder function. 19 Full-thickness rotator cuff tears often do not heal without treatment.…”
mentioning
confidence: 99%
“…Rotator cuff tears are among the most common causes of pain and functional disability in the shoulder and commonly affect the supraspinatus tendon. 5 , 7 , 9 , 18 , 20 Integrity of the supraspinatus is vital for overhead shoulder function. 19 Full-thickness rotator cuff tears often do not heal without treatment.…”
mentioning
confidence: 99%
“…Anchors pulled out of cancellous bone 18% of the time at an average of 4300 cycles of the 10 -180 N load which is significantly greater than a RCR would be subjected to during the healing phase. A previous study of RCRs concluded that condition of the tissue or bone was the limiting reason for repair failure [15][16][17]. High UFLs and the high number of cycles before pullout of generic anchors from cancellous bone indicate the anchors will not be the limiting factor of RCRs.…”
Section: Discussionmentioning
confidence: 99%